1986
DOI: 10.1037/0022-0167.33.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Coping as a moderator of the relation between anxiety and career decision making.

Abstract: In this study, we examined relations among trait anxiety, coping types, career decision making, and state anxiety related to career decision making. The participants were 248 undergraduate students from a private university in the New York metropolitan area. Trait and state anxiety were measured by the State-Trait Anxiety Inventory (Form X; Spielberger, Gorsuch, & Lushene, 1970). Career decidedness or indecision was measured by the Vocational Decision Scale (Jones, 1977). Coping types were determined by an ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…For example, Wheeler (1983) measured occupational self-efficacy in terms of "Perceived Ability Match" and "Ease of Success" of various occupations; these approaches do not adequately capture the cognitive appraisal of future performance in Bandura's definition of self-efficacy. The measures employed in the studies by O'Hare and her colleagues (O'Hare & Beutell, 1987;O'Hare & Tamburri, 1986) are subject to similar criticisms. O'Hare and Tamburri (1986) adapted a work-coping scale to measure self-efficacy for coping with career decision making.…”
Section: Definitional and Measurement Problemsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Wheeler (1983) measured occupational self-efficacy in terms of "Perceived Ability Match" and "Ease of Success" of various occupations; these approaches do not adequately capture the cognitive appraisal of future performance in Bandura's definition of self-efficacy. The measures employed in the studies by O'Hare and her colleagues (O'Hare & Beutell, 1987;O'Hare & Tamburri, 1986) are subject to similar criticisms. O'Hare and Tamburri (1986) adapted a work-coping scale to measure self-efficacy for coping with career decision making.…”
Section: Definitional and Measurement Problemsmentioning
confidence: 95%
“…Two studies contain indirect implications for the link between selfefficacy and career decision making. O'Hare and her colleagues (O'Hare & Beutell, 1987;O'Hare & Tamburri, 1986) found that self-efficacy for coping with career decision-making tasks moderated the relationship between anxiety and career decision making. Higher levels of self-efficacy for coping with career decision making were predictive of lower anxiety and higher levels of decisiveness (O'Hare & Tamburri, 1986); men reported higher levels of confidence in their ability to cope with career decision making than women (O'Hare & Beutell, 1987).…”
Section: Self-efficacy and Career Decision-making Processesmentioning
confidence: 97%
“…Fuqua et al, 1988;Hartman et al, 1985), as far as we know, few studies have explored the influence of different forms of career anxiety on career indecision or career commitment (Daniels, Steewart, Stupnisky, Perry, & Lo Verso, 2011;Fuqua & Hartman, 1983;Leong & Chervinko, 1996;O'Hare & Tamburri, 1986;Weinstein, Healy, & Ender, 2002). In these studies, the participants used a modified state anxiety scale (STAY inventory, Spielberger, Gorsuch, & Luschene, 1983) to indicate how they feel when they are thinking about being decided or undecided about their career, or a scale to indicate how worried they are about their career choice (e.g., Daniels et al, 2011).…”
Section: Anxiety and Career Indecisionmentioning
confidence: 98%
“…Parmi eux, à la suite d'une étude longitudinale menée auprès de jeunes de seize ans qui intègrent le marché du travail pour la première fois, Jones (1985) conclut que ceux qui ont le sentiment de posséder les qualifications requises pour l'emploi sont plus confiants quant à leur possibilité d'insertion et sont plus actifs dans leur recherche d'emploi. O'Hare et Tamburi (1986), étudiant, pour leur part, la relation entre les comportements adaptatifs, le degré de détermi-nation vocationnel et le niveau d'anxiété, indiquent que les jeunes qui se sentent confiants et qui ont la maîtrise de leur devenir professionnel sont ceux-là mêmes qui sont les plus susceptibles de mener à bien leur cheminement de carrière.…”
Section: Létude Du Contexte Psychologiqueunclassified
“…Ainsi, il semble que les jeunes vont rencontrer des difficultés s'ils ne peuvent définir leur futur professionnel (Limoges, 1987;Nuttin, 1980), s'ils n'ont pas une perspective temporelle étendue (Forner, 1987;Fournier, Pelletier et Pelletier, 1993), s'ils ont des attentes irréalistes à l'égard du travail et des structures d'emploi (Fox et Krausz, 1982), s'ils ne sont pas familiers avec le processus de décision (Harren, 1979;Janis et Mann, 1977;O'Hare et Tamburi, 1986), et s'ils ne peuvent anticiper leurs réactions émotives face à l'intégration du marché du travail et face au stress qu'implique la situation de recherche d'emploi (Brennan, 1989;Hawkins, Bradley et White, 1977;Morneau, 1991).…”
Section: Létude Du Contexte Psychologiqueunclassified